Naqd-i ṣūfī - Afšārī, Mihrān,Ṣaḥrāʾī, Šahrām (Intišārāt-i Muʾassasa-i Farhangī - Hunarī-i Ǧahān-i Kitāb, 2023)
Afshārī, Mihrān – Interviews. ; Sufism in literature. ; Sufism – Iran
Keywords: Interview